Nursing Home Deficiency Citations for Physical Restraints and Restrictive Side Rails. (May 2013) - Wagner, Laura M.; McDonald, Shawna M.; Castle, Nicholas G.
This article examines whether nursing home facility-level characteristics are associated with the likelihood of receiving deficiency citations for physical restraints, including restrictive side rails. Data from the On-Line Survey Certification of Automated Records were used to calculate odds ratios for facility-level characteristics associated with these deficiency citations. Repeat records from 2000 to 2007 were combined to produce longitudinal data. The results of this study show that restraint/side rail deficiency citations were negatively associated with higher staffing levels of registered nurses and licensed practical nurses ( p ≤ .001) and higher Medicaid reimbursement rates ( p ≤ .01). Citations were positively associated with greater nurse aide staffing ( p ≤ .01) and higher quality-of-care deficiency citation percentiles ( p ≤ .001). The extent of physical restraint and restrictive side rail misuse within nursing homes appears to vary according to various facility characteristics. It is less clear how internal processes within a facility bring about these observed patterns of variation.